2021
DOI: 10.6018/rcsar.393181
|View full text |Cite
|
Sign up to set email alerts
|

Management’s choice of tone in letters to shareholders: sincerity, bias and incentives

Abstract: El objetivo de este artículo es identificar los factores que impulsan las decisiones de los directivos en materia de información en un entorno caracterizado por la concentración de la propiedad y la escasa aplicación de la ley. Investigaciones anteriores indican que el tono de la carta a los accionistas está correlacionado con los resultados. Sin embargo, el tono puede estar sesgado hacia lo positivo cuando una empresa es muy sensible a los incentivos del mercado de valores o está controlada por inversores may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In this sense, as Yamane and Kaneko (2021) showed, raising stakeholder awareness of the SDGs leads private companies to engage in SDG implementation. In particular, due to the increase in the institutional investors' participation in listed companies' ownership, which ascends to more than 40% (Organisation for Economic Co‐operation and Development ‐ OECD, 2020), they significantly influence corporate strategies, including SDG engagement and reporting (Calza et al, 2016; García‐Sánchez, Rodríguez‐Ariza, Aibar‐Guzmán, & Aibar‐Guzmán, 2020; Hadro et al, 2021; Jonsdottir et al, 2021; Melón‐Izco et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, as Yamane and Kaneko (2021) showed, raising stakeholder awareness of the SDGs leads private companies to engage in SDG implementation. In particular, due to the increase in the institutional investors' participation in listed companies' ownership, which ascends to more than 40% (Organisation for Economic Co‐operation and Development ‐ OECD, 2020), they significantly influence corporate strategies, including SDG engagement and reporting (Calza et al, 2016; García‐Sánchez, Rodríguez‐Ariza, Aibar‐Guzmán, & Aibar‐Guzmán, 2020; Hadro et al, 2021; Jonsdottir et al, 2021; Melón‐Izco et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, as Yamane and Kaneko (2021) showed, raising stakeholder awareness of the SDGs leads private companies to engage in SDG implementation. In particular, due to the increase in the institutional investors' participation in listed companies' ownership, which ascends to more than 40% (Organisation for Economic Co-operation and Development -OECD, 2020), they significantly influence corporate strategies, including SDG engagement and reporting (Calza et al, 2016;Hadro et al, 2021;Jonsdottir et al, 2021;Mel on-Izco et al, 2021). Indeed, introduced in April 2006, the United Nations Principles for Responsible Investment (UN PRI) establish commitments to incorporate social, environmental, and governance criteria into investment decisions (Cohen et al, 2011), encouraging Socially Responsible Investment (SRI) and investors' activism to promote sustainability in the companies in which they invest (García-Sánchez, Aibar-Guzmán, & Aibar-Guzmán, 2020).…”
mentioning
confidence: 99%
“…The existing literature has found that corporate disclosure is overwhelmingly positive (Gibbins et al, 1990;Hadro et al, 2021;Hildebrandt & Snyder, 1981;Moreno, 2019). This consistent pattern could result in the tone of management reports losing any potential significance.…”
Section: H1mentioning
confidence: 86%
“…Information for the analysis and identification of the key issues was obtained through content and textual analysis [67,68]. Specifically, the information on the CE was all first disclosed by the companies on their corporate websites and is verbatim.…”
Section: Methodsmentioning
confidence: 99%